The genetic characterisation of a carbon starvation gene of Helicobacter pylori : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Microbiology at Massey University, Palmerston North, New Zealand - Beddek, Amanda Jane (Massey University, 1998)
The carbon starvation gene (csg) of the gastric pathogen Helicobacter pylori was studied to elucidate the role of the gene product during the carbon starvation response. Studies were also conducted to investigate the relationship of csg to the glutamine permease operon (glnP1, glnP2, glnQ, and glnH), which is located directly upstream of csg on the H. pylori chromosome. csg and glnP1 were sequenced to determine the length of the genes, the base composition, and the location of putative promoters and regulator binding sites. The sequence information was then used to construct a csg mutant using a deletion insertion strategy, whereby the promoter regions of csg and glnP1 were removed and replaced with the KanΩ antibiotic resistance marker. Phenotypic analysis was carried out on this mutant in complex, defined, and semi-defined media. The plasmid carrying the csg mutation was also transformed into H. pylori Sydney strain to allow colonisation studies in mice. A H. pylori strain was constructed, which would allow the study of the expression of csg under various environmental conditions. The promoterless chloramphenicol acetyl transferase (CAT) cassette from pCM4 was used as the reporter gene and cloned into an engineered BglII site directly downstream of csg to disrupt the transcription terminator. The kanamycin resistance cassette from pILL600 was also cloned into this site in a three way ligation, to allow selection of transformants in H. pylori. Sequence of the csg mutant showed putative σ 70 responsive -10 and -35 sequences, and a putative cAMP receptor protein (CRP) binding sequence for csg in the 5' sequence of glnP1. The CRP site implied that csg may be regulated by cAMP. The location of the CRP binding site also suggested that csg and glnP1 were linked, which was confirmed by PCR amplification of a region containing the csg and glnP1 transcription start points and the intergenic region from ten H. pylori strains. The same PCR amplification failed for a H. mustelae strain, suggesting that this conservation of sequence is specific to H. pylori strains. Phenotypic analysis of the csg mutant showed no difference compared to the wild type when grown in complex and semi-defined medium, both of which contained peptides. However, the csg mutant grew more slowly than the wild type in the defined medium, which contained glucose and amino acids as the sole carbon sources. The role of csg could not be determined with certainty. The results suggested that Csg may scavenge for carbon sources to help the cell escape carbon starvation. This thesis work has shown csg to be non-essential in vitro. However, a non-functional csg gene in vivo may impair transmission, when carbon sources are lacking, but the mutation would be silent in the stomach where peptides are abundant.
Keywords: Helicobacter pylori; Genetics